BIVPLENT METAL COMPLEXES OF SODIUM ASCORBATE (Journal of Sciences, Islamic Republic of Iran)
The mode of coordination of8 manganese(fI), cobaltm, nickel(H), copper(II), zinc(H), lead(II) and cadmium(I1) to sodium ascorbate (NaHAsc) was investigated using IR, UV-visible, AAS, elemental microanalyzer, conductivity, magnetic and 'M and I3C NMR spectroscopic studies, NaNAsc is bidentate and coordination was through the carbonyl group and the oxygen atom of carbon-2 enolic hydfoxyl group, The complexes are mainly high spin octahedral complexes based on the magnetic moment and spectral data.